2007
DOI: 10.1890/06-1847.1
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Nitrogen Limitation Increases Decomposition

Abstract: With anthropogenic nutrient inputs to ecosystems increasing globally, there are long-standing, fundamental questions about the role of nutrients in the decomposition of organic matter. We tested the effects of exogenous nitrogen and phosphorus inputs on litter decomposition across a broad suite of litter and soil types. In one experiment, C mineralization was compared across a wide array of plants individually added to a single soil, while in the second, C mineralization from a single substrate was compared ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

39
445
7
4

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 816 publications
(515 citation statements)
references
References 33 publications
(36 reference statements)
39
445
7
4
Order By: Relevance
“…However, the addition of N did not cause the priming response in this experiment, as (a) the two litters caused different directions of priming, and (b) the substrate with the lowest C:N ratio (Table 1) and highest inorganic N concentrations (Table 3) had the strongest soil-priming response (Fig. 2), inconsistent with a mechanism of priming driven by microbial 'mining' of the soil for N after the addition of C (Fontaine et al, 2003;Moorhead and Sinsabaugh, 2006;Craine et al, 2007). However, the litter additions may have impacted the increase in priming in response to soil temperature, as the higher N content of the soil-litter mixtures may have allowed for the production of a larger number of hydrolytic enzymes Cusack et al, 2011), or a suite of more efficient enzymes (Stone et al, 2012), that were capable of degrading more soil-C as the temperature increased.…”
Section: Discussionmentioning
confidence: 63%
“…However, the addition of N did not cause the priming response in this experiment, as (a) the two litters caused different directions of priming, and (b) the substrate with the lowest C:N ratio (Table 1) and highest inorganic N concentrations (Table 3) had the strongest soil-priming response (Fig. 2), inconsistent with a mechanism of priming driven by microbial 'mining' of the soil for N after the addition of C (Fontaine et al, 2003;Moorhead and Sinsabaugh, 2006;Craine et al, 2007). However, the litter additions may have impacted the increase in priming in response to soil temperature, as the higher N content of the soil-litter mixtures may have allowed for the production of a larger number of hydrolytic enzymes Cusack et al, 2011), or a suite of more efficient enzymes (Stone et al, 2012), that were capable of degrading more soil-C as the temperature increased.…”
Section: Discussionmentioning
confidence: 63%
“…It is proposed that during later stages, lignolytic enzyme efficiency maybe limited by high N content or by high availability of inorganic N (Ågren et al, 2001;Berg, 1986;Berg et al, 1998;Fog, 1988;Hagedorn et al, 2003;Magill and Aber, 1998;Micks et al, 2004). This is also supported by the results found in laboratory experiments (Craine et al, 2007).…”
Section: Discussionmentioning
confidence: 74%
“…The decomposition of litter with higher N concentration may respond differently to further N deposition, as substrate quality strongly influences the rates of decay (Berg and Eckbohm, 1991;Berg and Matzner, 1997;Cleveland et al, 2006) and net N release from decomposing litter is overwhelmingly driven by the initial N status (Parton et al, 2007). Results from laboratory experiments showed that low soil N availability can increase litter decomposition but high soil N supply or substrate N concentration decrease litter decomposition due to "microbial N mining" (Craine et al, 2007). However, to our knowledge, information regarding the decomposition response of litter to increased N deposition from the same species but with different nutrient-status is non-existent.…”
Section: Introductionmentioning
confidence: 99%
“…Low N availability can increase CO 2 -C loss during litter decomposition as microorganisms use labile residues to acquire N from recalcitrant substrates (Craine et al, 2007). Thus, N availability controls the C-use efficiency of decomposers such that substrates with low initial C:N ratio increase efficiency, and N-poor substrates (high C:N) lead to a less-efficient use of C (Manzoni et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, N availability controls the C-use efficiency of decomposers such that substrates with low initial C:N ratio increase efficiency, and N-poor substrates (high C:N) lead to a less-efficient use of C (Manzoni et al, 2008). The CO 2 -C loss from increased heterotrophic respiration under low C-use efficiency can be alleviated by high soil N supply (Craine et al, 2007), with consequent gains in organic C stabilization in SOM (Bird et al, 2003;Moran et al, 2005;Kirkby et al, 2013;Kirkby et al, 2014). An increase in C-use efficiency by microorganisms can favor the contributions of microbial residues to the SOM fractions associated with minerals (Cotrufo, 2013), assumed to be the fractions of greater stability in SOM.…”
Section: Introductionmentioning
confidence: 99%